Performance Comparison of Ground Improvement Methods for Settlement Reduction (Case Study: 5000M³ Fuel Tank) - Muhammad Bintang Kurniadi; Hermawan Dermawan; Naufal Ariq Pratama (Politeknik Negeri Lhokseumawe, 2025)
This study compares the effectiveness of three soil improvement methods—Stone Column, Modular Grout Column (MGC), and Deep Soil Mixing (DSM)—in reducing settlement for a 5000 m³ fuel tank. Using a 2D numerical modeling approach, the settlement reduction for each method was analyzed. The results showed that MGC was the most effective, achieving a 52% reduction in settlement, followed by Stone Column (47%) and DSM (39%). These findings emphasize the importance of selecting the appropriate soil improvement method based on soil conditions. For optimal results, increasing column diameter is recommended.